2023
DOI: 10.1021/jacs.2c12631
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Expression and Chemical Amidation of Isotopically Labeled Native Melittin

Abstract: Post-translational modifications are ubiquitous in the eukaryotic proteome. However, these modifications are rarely incorporated in NMR studies of eukaryotic proteins, which are typically produced through recombinant expression in E. coli. Melittin is the primary peptide in honey bee venom. Its native C-terminal amide significantly affects its equilibrium structure and dynamics in solution and is thus a prerequisite for studying its native structure and function. Here, we present a method for producing triply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Melittin, the active component of honeybee venom, is a 26-residue peptide containing a post-translational C-terminal amidation (section II of the Supporting Information) that undergoes exchange between an intrinsically disordered monomer and an α-helical tetramer at millimolar peptide concentrations. Residual dipolar couplings (RDCs) measured in solution showed the same helical structure for the tetramer as observed via X-ray crystallography and predicted by AlphaFold-Multimer . The melittin tetramer forms on the millisecond time scale from monomers with residue P14 in the trans conformation, while there is also a much slower off-pathway exchange between disordered monomers with P14 in the trans and cis conformations.…”
supporting
confidence: 59%
See 3 more Smart Citations
“…Melittin, the active component of honeybee venom, is a 26-residue peptide containing a post-translational C-terminal amidation (section II of the Supporting Information) that undergoes exchange between an intrinsically disordered monomer and an α-helical tetramer at millimolar peptide concentrations. Residual dipolar couplings (RDCs) measured in solution showed the same helical structure for the tetramer as observed via X-ray crystallography and predicted by AlphaFold-Multimer . The melittin tetramer forms on the millisecond time scale from monomers with residue P14 in the trans conformation, while there is also a much slower off-pathway exchange between disordered monomers with P14 in the trans and cis conformations.…”
supporting
confidence: 59%
“…Molecular dynamics simulations have suggested that melittin forms partially disordered tetramers by sequential addition of monomers in <300 ns that later relax into a well-ordered crystal-like structure. , We see no evidence from chemical shifts, RDCs, or relaxation measurements for exchange between a rigid and partially disordered tetramer at early time points . Furthermore, dimer–dimer addition has been observed to be ubiquitous in nature for homotetramer formation, possibly due to selective evolutionary pressure to avoid unwanted buildup of trimer species .…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Novel approaches for predicting a protein’s structure from its amino acid sequence frequently can generate atomic resolution models that rival or exceed the quality of experimentally determined structures. An extension of one of these computational methods, AlphaFold, yielded the powerful AlphaFold2 and AlphaFold-Multimer programs, , which have been shown successful at correctly predicting the atomic resolution structures of well-defined oligomeric complexes. However, no unique predictions are generally available for proteins that do not adopt a distinct oligomeric state of a well-defined size, as is often seen during the initial aggregation process of proteins implicated in amyloid diseases, prior to the formation of highly ordered fibril species.…”
Section: Introductionmentioning
confidence: 99%